Architecture and art - Jarocka, Aleksandra (Budownictwo i Architektura / Civil and Architectural Engineering, 2010)
This article presents a perception of architecture in the context of an art. Juxtaposing the terms “architecture” and “art,” explaining them and presenting their mutual correlations contributes to deeper comprehension of the subject issue. Thanks to such an operation, the author of this article proves that, in spite of immense discrepancies of opinions published in the Internet, the typically technical discipline of science can also enchant us with its esthetic values. Although a major part of edifices situated in our environment are only hollow and soulless projections, there are still numerous places in the world that can be distinguished only thanks to outstanding premises, namely Sydney Opera. The article provides also a deep insight into various theses proving that both architects and artists look for an inspiration in the surrounding world, especially in the nature itself. In order to corroborate the aforementioned statements, the author of this paper mentions works of such architects as Jean Nouvel, Mies van der Rohe and Diller + Scofidio. However, there are still some designers who claim that architecture cannot be combined with art, since these two disciplines are completely different and have nothing in common with each other.